2020
DOI: 10.1111/iwj.13486
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of chronic wounds in nursing homes in Germany

Abstract: The burdens caused by chronic wounds on the affected persons themselves and also on the health care system are well recognised. The aim of this study was to investigate the prevalence and risk factors of chronic wounds in German nursing homes. An annual cross‐sectional study was conducted in nursing home residents from 2012 to 2018. The proportion of men affected by chronic wounds was to some extent higher than that of women, 9.0% males vs 7.5% females. In total, 7.8% of all residents were affected by chronic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 33 publications
4
25
2
2
Order By: Relevance
“…25 Being underweight was also associated with wounds. 47 Studies have contradictory findings regarding obesity, perhaps due to the wound type 32,48 and we did not find an independent association. The growing evidence of the connection between obesity and lymphoedema 37 is worthy of further investigations.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…25 Being underweight was also associated with wounds. 47 Studies have contradictory findings regarding obesity, perhaps due to the wound type 32,48 and we did not find an independent association. The growing evidence of the connection between obesity and lymphoedema 37 is worthy of further investigations.…”
Section: Discussioncontrasting
confidence: 74%
“…40 We found that being male had a greater association with wounds than diabetes. Male predominance has been reported in chronic wounds, 47 VLU, 26,27 and DFU. 31,32 Yet, contradictory results for VLU have been reported 28,48 and sex was not a risk factor in pressure ulcers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar to our results, some previous studies also reported that sex cannot be regarded as an independent risk factor for decubitus ulcers development, and the differences regarding decubitus ulcers prevention interventions seem to be minimal 4 , 13 . However, some studies have shown that the prevalence of decubitus ulcers in men may be higher than that in women 10 , 14 . According to their opinions, smoking was more common in men than women.…”
Section: Discussionmentioning
confidence: 98%
“…The interruption in the healing process may occur for a number of reasons connected to one's lifestyle and health condition. For example, smoking, malnutrition, obesity, low mobility, neuropathy, diabetes, vascular diseases and skin disorders have been linked to the increasing chronicity of wounds, where healing has not been achieved within 3-6 weeks [2][3][4].…”
Section: Wound Healing and Electrospun Wound Dressingsmentioning
confidence: 99%